Flags of Convenience in Cruise Tourism: Is It an Opportunity or an Exploitation of Developing Countries? - Putu Titah Kawitri Resen; Ade Devia Pradipta; Ismar Ramadhani (Soshum: Jurnal Sosial dan Humaniora, 2021)
The purpose of this article is to highlight the power relations between transnational corporations and developing countries due to the application of the Flags of Convenience (FoC) system in the cruise tourism industry. The focus is to answer whether the FoC in global cruise tourism is a good opportunity or actually a system that exploits developing countries. This article uses literature review method by referring to the concept of power of transnational corporations as an analytical framework. This study found that the FoC system strengthens the position of non-state actors in the international system through its regulations and by achieving its business goals through its power over the country, particularly developing countries.